A microbead-enhanced electrochemical platform for β-amyloid peptide (1–42) detection - Razzino, Claudia do Amaral; Sgobbi, Lívia Flório; Cancino-Bernardi, Juliana; Zapata, Angelica Maria Mazuera; Costa, Clara Cardoso; Zucolotto, Valtencir; Vieira, Lucia; Lobo, Anderson Oliveira (Frontiers in Sensors, 2024)
Alzheimer’s disease is the most prevalent form of dementia and is primarily characterized by the accumulation of β-amyloid and phosphorylated tau proteins in the brain, along with the degeneration of nerve cells, which leads to impairment of various cognitive functions. A significant biomarker of Alzheimer’s disease is the decreased level of soluble β-amyloid peptide (1–42) (Aβ1-42) in cerebrospinal fluid (CSF), as pathology progresses when CSF-Aβ1-42 levels drop below 192 pg mL−1. In this study, we developed an amperometric immunosensor based on magnetic beads as the platform for constructing the immunosensor. Monoclonal antibodies are immobilized on the MBs, enabling selective detection of Aβ1-42. The detection antibody is conjugated with the enzyme horseradish peroxidase, which, in the presence of H2O2 and hydroquinone, catalyzes the decomposition of H2O2 and the oxidation of hydroquinone to p-quinone, generating an electric current measured at a potential of −200 mV (vs. the Ag pseudo-reference electrode) using screen-printed carbon electrodes. The amperometric sandwich-type immunosensor demonstrates a linear response in the concentration range of 10 to 10,000 pg mL−1, with a detection limit of 7.4 pg mL−1, exhibiting excellent selectivity against the assessed interferents. These findings suggest the potential application of this immunosensor in the early diagnosis of Alzheimer’s disease, offering a sensitive and specific tool for clinical analysis. Despite its high performance, further studies are required to validate its robustness and applicability in complex clinical samples.